PEMANFAATAN LIMBAH TERNAK DALAM MENINGKATKAN PRODUKTIVITAS PERTANIAN DESA BOJONGSARI KECAMATAN ALIAN KABUPATEN KEBUMEN (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Processing livestock waste is an effort that provides many benefits. On the other hand, processing provides financial benefits because processing produces marketable products. Livestock waste has various benefits, such as animal feed, organic fertilizer, energy source and medium for other purposes. Processing of livestock waste depends on the type/species of livestock, number of livestock, maintenance procedures, available area and target use of the waste. For use, solid waste can be processed into manure, green manure, bokashi and compost. Meanwhile, liquid waste processing can be processed physically, chemically and biologically. Counseling and discussion methods are the methods used in this service with the target activities being livestock groups and local residents. This activity was carried out in Bojongsari Village, Alian District, Kebumen Regency. The result of the service activities is that farmers understand better how to process livestock waste so that the economic value is higher and they have knowledge of managing livestock waste correctly and environmentally friendly.